2015
DOI: 10.3233/bmr-150590
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measurements of the extension-flexion ratio with surface EMG

Abstract: The measurement of the extension-flexion ratio performed with the use of sEMG shows high level of intra- and inter-session reliability, suggesting that this parameter is a reliable tool in evaluation of the lumbar paraspinal muscles activity. However, the level of typical error should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this field, the available sEMG-based indices assessing muscle activation, symmetry and localized fatigue can be used to support the selection of the therapeutic exercises and to monitor their effectiveness over time ( 161 ). In patients with low back pain (LBP), sEMG has been used as a tool for functional diagnosis and to assess the effectiveness of treatment ( 162 , 163 ) and manipulation ( 164 ). Two systematic reviews are available on this topic ( 164 , 165 ), which concluded that sEMG-based parameters of amplitude and localized fatigue are useful tools to monitor the effect of different interventions delivered to relieve LBP.…”
Section: Surface Emg Applicationsmentioning
confidence: 99%
“…In this field, the available sEMG-based indices assessing muscle activation, symmetry and localized fatigue can be used to support the selection of the therapeutic exercises and to monitor their effectiveness over time ( 161 ). In patients with low back pain (LBP), sEMG has been used as a tool for functional diagnosis and to assess the effectiveness of treatment ( 162 , 163 ) and manipulation ( 164 ). Two systematic reviews are available on this topic ( 164 , 165 ), which concluded that sEMG-based parameters of amplitude and localized fatigue are useful tools to monitor the effect of different interventions delivered to relieve LBP.…”
Section: Surface Emg Applicationsmentioning
confidence: 99%
“…Surface EMG has been extensively used with the low back muscles. Its validity as well as its reliability have been shown in different functional tasks (Czaprowski et al 2015;Lariviere et al 2008;Mohseni Bandpei et al 2014…”
Section: Data Acquisitionmentioning
confidence: 99%